PERSEPSI JAJARAN PIMPINAN TENTANG KAWASAN TANPA ROKOK ( KTR ) DI DINAS KESEHATAN KABUPATEN LANGKAT TAHUN 2014 - ilham khairi; R. Kintoko Rochadi; Tukiman, MKM (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACTNo Smoking Area is a place or area that prohibited for production, sales, advertising, promotion and use of cigarettes activities. Determination of No Smoking Area is an effort to protect the public against the risk of health problems due to the threat of contaminated environment. This is background of researcher to conduct the research with using a qualitative studies to identify and understand the perception of the leadership ranks at the District Health Office Langkat about No Smoking Area year 2014 because the leadership is the people who are influential in establish a policy to be determined.This study uses a qualitative approach that utilizes a data collection technique with in-depth interviews to six-person as informant.The results showed all informants are agreeing on the No Smoking Area in District Health Office Langkat because it has a positive impact especially in health sector. Informants also had a strong commitment to realize it. The policy draft regarding to No Smoking Area expressed by several informants in written rules and sanctions, it starts with the appeal and the to awareness by using the health promotion steps. Therefore, researcher suggest that the Leadership ranks to sets the No Smoking Area immediately and dissemination of guidelines for implementation of the No Smoking Area.Keyword = perception, leadrship ranks, smoke and no smoking area.